Clinical effects of toxic and non-toxic doses of biological and chemical silver nanoparticles on rats' neonate kidney - Behrooz Yahyaei; Parastoo Pourali; Tana Heidari (Fiyz̤, 2020)
Background: Silver has long been known for its antibacterial properties. With the increasing use of silver nanoparticles in various consumer and medical products, it is necessary to check the toxicity of silver nanoparticles for the safety of users. Materials and Methods: This study was done on the female Wistar rats. These rats were divided to 5 groups such as the control and four treatment groups. Toxic dose was determined based on IC50. For the biological nanoparticles, the non-toxic dose was 3-4 ml and the toxic dose was 6-8 ml. For the chemical nanoparticles, the non-toxic dose was 2.5 ml and the toxic dose was 5 ml. Injections were performed in the last two weeks of gestation and sampling was performed two weeks after birth. Then histological study of renal changes in the cortical and medulla and details of each area were performed by two incisions. Results: This test was showed that the nonpoisonous of chemical nanoparticles slightly caused the hyperemia and inflammation in renal cells. Injection of poisonous chemical nanoparticles caused serious change renal tissue. In injection of poisonous and nonpoisonous biological didnchr('39')t changes tubular cells but caused little changes in renal tissue. Conclusion: The facing with the chemical silver nanoparticles during the pregnancy related to the different dosage of silver nanoparticles induced the poison in the kidney of offspring rats. Biological nanoparticles have the less effect on the renal tissue despite of the chemical ones.